Dynamics of a stochastic prey–predator eco-epidemiological system with distributed delay and impulsive perturbations - Dai, Xiangjun; Jiao, Jianjun; Quan, Qi; Zhou, Zeli (Mathematics and computers in simulation, 2026)
A stochastic prey–predator eco-epidemiological model with distributed delay and impulsive perturbations is proposed and studied. The existence and uniqueness of the global positive solution are studied. The pth moment boundedness and the asymptotic pathwise estimation are discussed. And then, the sufficient conditions for the extinction, stability in the mean and the global attractivity of the system are given. Finally, some numerical examples are presented to validate our main theoretical findings. Our results indicate that the impulsive perturbations do not influence the survival of the population when the impulsive perturbations are bounded. However, the extinction and the stability in the mean of the population can change significantly when the impulsive perturbations are periodic. Furthermore, the distributed delay has no effect on the extinction, stability in the mean and global attractivity of the system whether the impulsive perturbation is bounded or periodic.